The Relationship between Multiple Role Conflict and Work Stress among Midwives - Ni Putu Ika Palmasari; Luh Putu Ratih Andihini; Nyoman Trisna Aryanata (Psikologi Prima, 2025)
Midwives are a profession with high physical and psychological demands, especially for those who are married, have children, and remain actively working, thus having to perform dual roles as professionals and homemakers, which can lead to work stress. This study aims to examine the relationship between dual role conflict and work stress among midwives at Hospital X in Gianyar Regency, who are members of the IBI Sanjiwani Branch. The method used was quantitative with a cross-sectional approach, involving 30 purposively selected midwives who were married, actively working, and had children aged 0–15 years.The instruments used were the dual role conflict scale and the work stress scale, both with adequate validity and reliability. Data analysis using the Spearman correlation test showed a significant positive relationship between dual role conflict and work stress, with r = 0.402 (p < 0.05). The highest conflict aspect was strain-based FIW (Family Interfering with Work), and the most prominent work stress aspects were psychological and behavioral. These findings highlight the importance of role management, work–family balance, and support from both organizations and families in reducing midwives work stress.